Respostas
respondido por:
4
a1=-16
an=84
r=a2-a1=-14-(-16)=-14+16=2
an=a1+(n-1).r
84=-16+(n-1).2
84=-16+2n-2
84+16+2=2n
2n=102
n=102/2
n=51
Sn=(a1+an).n/2
S51=(-16+84).51/2
S51=68.51/2
S51=34.51
S51=1734
A soma é igual a 1734.
an=84
r=a2-a1=-14-(-16)=-14+16=2
an=a1+(n-1).r
84=-16+(n-1).2
84=-16+2n-2
84+16+2=2n
2n=102
n=102/2
n=51
Sn=(a1+an).n/2
S51=(-16+84).51/2
S51=68.51/2
S51=34.51
S51=1734
A soma é igual a 1734.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás